Minang Folklore of Pencak Arts to Strengthen Mental Health in Indonesian Muslim Society - Rustiyanti, Sri; Listiani, Wanda; Ema M.N, Anrilia (Mudra Jurnal Seni Budaya, 2023)
Pencak silat is one of Indonesia's cultural identities, recognized by UNESCO as an Intangible Cultural Heritage. Apart from being a martial arts defence, Pencak silat also contains the values of local wisdom textually and contextually. Pencak silat in Indonesia comes from 2 regions: Minangkabau (West Sumatra) and Cimande (West Java).  This research discusses the study of martial arts as a medium of self-defence and traditional educational media in Minangkabau, West Sumatra. A Minangkabau youth must learn martial arts and learn to read the Quran in a mosque (surau) as a provision for a man who has grown up if he wanders to other areas. The Minangkabau community in ancient times had two important educational institutions, namely surau and sasaran silat. Location of Surau (masjid) and sasaran silat usually side by side. In surau, young people learn to read the Al-Quran and religious knowledge, while in sasaran silat, they learn martial arts and various arts. Islamic teachings during the Minangkabau community have succeeded for generations in supporting the philosophy of life: 'adat bersandi syara'- syara' bersandi kitabullah'. This philosophy has been ingrained since birth, strengthening the mental health of youth and coloured in the daily life of the Minangkabau people. In other words, the embodiment of Islamic culture folklore minang can be seen in the life of the Minangkabau people. This made Minangkabau martial arts develop and spread in various parts of Indonesia.